An In Vivo Perspective of the Role(s) of the Alternative Oxidase Pathway. (March 2018) - Del-Saz, Néstor Fernández; Ribas-Carbo, Miquel; McDonald, Allison E.; Lambers, Hans; Fernie, Alisdair R.; Florez-Sarasa, Igor
Abstract : Despite intense research on the in vitro characterization of regulatory factors modulating the alternative oxidase (AOX) pathway, the regulation of its activity in vivo is still not fully understood. Advances concerning in vivo regulation of AOX based on the oxygen-isotope fractionation technique are reviewed, and regulatory factors that merit future research are highlighted. In addition, we review and discuss the main biological functions assigned to the plant AOX, and suggest future experiments involving in vivo activity measurements to test different hypothesized physiological roles. Highlights: Understanding the regulation of the alternative oxidase pathway (AOP) is important because its activity greatly reduces the energy efficiency of plant respiration. The possibility to measure in vivo AOP activity (νalt ) allows its study all the way from gene expression to its role in vivo . νalt is mostly tuned at the post-translational level, but this regulation is not fully understood. The combination of metabolomics with νalt measurements is shedding light on AOX regulation. In vivo evidence suggests that the AOP provides flexibility in cellular energy and carbon metabolism under stress conditions. However, there is also an important contribution of AOP under non-stress conditions which deserves further research.